Hero me not : the containment of the most powerful black, female superhero - Burke, Chesya (Rutgers University Press, 2023)
"If you ask a comic book reader to name a Black woman superheroine, most would point to the character of Ororo Munroe - Storm from the X-Men. Although there are a small number of other Black women superheroes, such as Spectrum, Vixen, and Friction, usually only avid comic book readers can name characters other than Storm. She is often the only recognizable Black, female superheroine and therefore is seemingly the one representative Black woman in the comic book/superhero world. Whether purposefully or not, the absence of Black women in the imaginary of the mostly white and male dominated field of comics has the profound effect of erasure and devaluing of Black women who not only do not have the opportunity to see themselves within these popular mediums, but who seek to move outside the standard submissive positions Black women are often placed in. Hero Me Not examines the multifaceted dimensions of the comic book character Storm from the X-men within the framework of Black feminist theory. Author Chesya Burke argues that this understanding of the depiction of Storm is essential to understanding the representation of black women's lives within the media and its effects on Black women readers. In exploring the ways in which Storm's character both frees and limits her, Burke takes the discussion back to the broader stereotype of the Magical Negro that led to Storm. Each chapter focuses on the incarnations of Storm's development over the years, while integrating contemporary racial politics culminating in discussion of the character called the Negro Spiritual Woman. Black women creators have come on scene in recent years, creating more interesting characters that are more empowered, and resistant to the status quo. While these characters are still few and far between, they have opened the door to better representation and less contained black women characters. Hero Me Not offers critical insight and hope for the development of Black women characters for casual and avid comic readers alike"-- Provided by publisher.
Keywords: Storm -- (Fictitious character); Women superheroes.; Superheroes, Black.; Women, Black, in popular culture.; Comic books, strips, etc. -- United States -- History and criticism.; Superhéroïnes.; Superhéros noirs.; Femmes noires dans la culture populaire.; LITERARY CRITICISM / General.; Comic books, strips, etc.; Superheroes, Black; Women, Black, in popular culture; Women superheroes; United States; ororo munroe, storm, x-men, comics, marvel, media studies, comic studies, africana studies, feminist, women, superhero, negro spiritual, stereotype.; Electronic books.; Criticism, interpretation, etc.